Scaphocapitolunate Arthrodesis and Radial Styloidectomy for Posttraumatic Degenerative Wrist Disease - Klausmeyer, Melissa A.; Fernandez, Diego L.; Caloia, Martin (Journal of Wrist Surgery, 2012)
Long-standing scaphoid nonunion, scaphoid malunion, and chronic scapholunate dissociation result in malalignment of the carpal bones, progressive carpal collapse, instability, and osteoarthritis of the wrist. The most commonly used procedures to treat scaphoid nonunion advanced collapse (SNAC) and scapholunate advanced collapse (SLAC) wrists are the four-corner fusion (4CF) and the proximal row carpectomy (PRC). The purpose of this study was to evaluate the clinical outcome of a different treatment modality: radial styloidectomy and scaphocapitolunate (SCL) arthrodesis. This treatment option is chosen in an effort to maintain the joint contact surface and load transmission across the radiocarpal joint. We conducted a retrospective review of 20 patients (average age 62 years, range: 27 to 75 years) treated from 1994 to 2010. Seven patients were treated for SNAC, 12 patients for SLAC wrists, and 1 for degenerative joint disease following a transscapho-transcapitate perilunar dislocation. Sixteen patients had Herbert screw fixation, and four had Spider plate fixation. All patients had autologous bone graft used for the arthrodesis. The mean follow-up was 4.6 years (range: 2 to 9.6 years). Patients were evaluated clinically and radiographically. Nineteen of 20 arthrodeses healed on an average of 9.6 weeks. One patient was reoperated 8 months after the initial operation with salvage of the SCL arthrodesis with a spider plate with an adequate result. The mean active flexion–extension arc was 70 degrees and the radioulnar deviation arc was 23 degrees. Pain decreased in all patients, 13 of whom were pain free postoperatively. The average postoperative disabilities of arm, shoulder, and hand score was 24. Radiographically, neither radiolunate nor radioscaphoid arthritis was noted on follow-up. SCL arthrodesis with radial styloidectomy resulted in an adequate residual range of motion and pain relief. This method preserves the normal ulnar sided joints of the carpus and maintains a more physiologic joint surface for radiocarpal load sharing.
Keywords: scaphocapitolunate; wrist arthrodesis; SNAC; SLAC